Insights Into Extracellular Vesicle/Exosome and miRNA Mediated Bi-Directional Communication During Porcine Pregnancy - Bidarimath, Mallikarjun; Lingegowda, Harshavardhan; Miller, Jessica E.; Koti, Madhuri; Tayade, Chandrakant (Frontiers in Veterinary Science, 2021)
Spontaneous fetal loss is one of the most important challenges that commercial pig industry is still facing in North America. Research over the decade provided significant insights into some of the associated mechanisms including uterine capacity, placental efficiency, deficits in vasculature and immune-inflammatory alterations at the maternal-fetal interface. Pigs have unique epitheliochorial placentation where maternal and fetal layers lay in opposition without any invasion. This has provided researchers opportunities to accurately tease out some of the mechanisms associated with maternal-fetal interface adaptations to the constantly evolving needs of a developing conceptus. Another unique feature of porcine pregnancy is the conceptus derived recruitment of immune cells during the window of conceptus attachment. These immune cells in turn participate in pregnancy associated vascular changes and contribute towards tolerance to the semi-allogeneic fetus. However, the precise mechanism of how maternal-fetal cells communicate during the critical times in gestation is not fully understood. Recently, it has been established that bi-directional communication between fetal trophoblasts and maternal cells/tissues is mediated by extracellular vesicles (EVs) including exosomes. These EVs are detected in a variety of tissues and body fluids and their role has been described in modulating several physiological and pathological processes including vascularization, immune-modulation and homeostasis. Recent literature also suggests that these EVs (exosomes) carry cargo (nucleic acids, protein, and lipids) as unique signatures associated with some of the pregnancy associated pathologies. In this review, we provide overview of important mechanisms in porcine pregnancy success and failure and summarize current knowledge about the unique cargo containing biomolecules in EVs. We also discuss how EVs (including exosomes) transfer their contents into other cells and regulate important biological pathways critical for pregnancy success.